The Politics of Agricultural Policy-making in Canada - Skogstad, Grace, 1948- (Book collections on Project MUSE., 1987)
From her three case studies emerges a well-defined analysis of the processes of policy-making and roles of the various participants. Skogstad illustrates the origins of federal-provincial as well as interprovincial disagreements.